Analisis Resepsi Kader PKB Bandung Terhadap Isu Reformasi Birokrasi pada Pidato Pelantikan Presiden di Televisi - Bagas Prawira; Heppy New Year Haloho (UNIVERSITAS KALBIS, 2022)
The President addressed this issue in his speech. This study seeks to determine how Bandung PKB party cadres responded to President Joko Widodo's second inaugural address's discussion of bureaucratic reform. This investigation employs the encoding-decoding theory and a constructivist methodology. The data collection technique for this qualitative study is in-depth interviews. This study classifies audience reception into three distinct categories: dominant-hegemony, negotiations, and opposition. The results of in-depth interviews indicate that each informant interprets the content of the speech differently. The differing perspectives of the five informants demonstrate this. One informant holds the Hegemony-Dominant position, two hold the Negotiation position, and the remaining two hold the Opposition position.